Combined flow in musical jam sessions: A pilot qualitative study. (March 2015) - Hart, Emma; Di Blasi, Zelda
Despite extensive research into the phenomenon of flow, there has been a comparative deficit in literature relating to the experience of shared or combined flow. This pilot study explored the subjective experience of combined flow in musical jam sessions, with particular emphasis on delineating the characteristics, outcomes, and practical applications unique to combined flow. In-depth semi-structured interviews were held with six musicians who had extensive experience of group jam sessions. Grounded theory analysis of interview data identified two major themes; the experience of combined flow as a sequential progression through a set of stages; and the inter-subjectivity of the experience leading to the development of empathy between group members. A major finding was that the combined flow experience discussed by musicians met many of the criteria for classification as a flow experience, while also having the unique positive outcome of empathy development.